To find q + 3, you need to answer this first:
What is 5-3?
5-3=2.
q would be equal to 2.
so now we have something like this:
1
_ ( 2 + 3) =5
3
--------------------------------------------------
Define x :
--------------------------------------------------
Let Cheryl be x years old.
Cheryl = x
Lisa = x + 6
--------------------------------------------------
In two years time:
--------------------------------------------------
Cheryl = x + 2
Lisa = x + 8
--------------------------------------------------
Lisa will be twice as old as Cheryl :
--------------------------------------------------
x + 8 = 2(x + 2)
--------------------------------------------------
Solve x :
--------------------------------------------------
x + 8 = 2(x + 2)
x + 8 = 2x + 4
x = 4
--------------------------------------------------
Find their age :
--------------------------------------------------
Cheryl = x = 4
Lisa = x + 6 = 4 + 6 = 10
--------------------------------------------------
Answer: Lisa is 10 years old now.
--------------------------------------------------
All of these choices would result in a 29-ft perimeter for the quilt.
But choice-b is significantly closer to the golden ratio than the others are.
Golden Ratio = (1/2) (1 + √5) = 1.618... (rounded)
Choice a). 1.665
Choice b). 1.617 the answer is "B"
Choice c). 1.526
Choice d). 1.5709
First can you tell me the difference in price
Answer:
g(-4) = -1
g(-1) = -1
g(1) = 3
Explanation:
If you are given a function that is defined by a system of equations associated with certain intervals of x, just find which interval makes x true, and then substitute x into the equation of that interval.
For example, given g(-4), this is an expression which is asking for the value of the equation when x = -4. So -4 is not ≥ 2, so ¼x - 1 will not be used. -4 is also not ≤ -1 and ≤ 2, so -(x - 1)² + 3 will not be used either. So in turn, we will just use -1 which is always -1 so g(-4) will just be -1, right because there is no x variable in -1 so it will always be the same.
Using the same idea as before g(-1) is g(x) when x = -1 so -1 will not be a solution because -1 is not less than -1 (< -1). -1 is not ≥ 2 either so we will be using the second equation because -1 is part of the interval -1≤x≤2 (it is a solution to this inequality), therefore -(x - 1)² + 3 will be used.
As x = -1, -(x - 1)² + 3 = -(-1 - 1)² + 3 = -(-2)² + 3 = -4 + 3 = -1.
It is a coincidence that g(-1) = -1.
Now for g(1), where g(x) has an input of 1 or the value of the function where x = 1, we will not use the first equation because x = 1 → x < -1 → 1 < -1 [this is false because 1 is never less than -1], so we will not use -1.
We will use -(x - 1)² + 3 again because 1 is not ≥ 2, 1≥2 [this is also false]. And -1 ≤ 1 < 2 [This is a true statement]. Therefore g(1) = -(1 - 1)² + 3 = -(0)² + 3 = 3